1999
DOI: 10.1063/1.1149572
|View full text |Cite
|
Sign up to set email alerts
|

Improved low-energy, electron-spin-polarized He+4 ion source

Abstract: Recent improvements to a source of electron-spin-polarized He+4 ions based on an optically pumped, rf-excited helium discharge are described that have resulted in ion polarizations P+ of ∼0.18 at currents of ∼1 nA and in an increase of over an order of magnitude in the quality factor P+2I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…The spin-polarized He + ions were generated from Penning ionization of spin-polarized He 2 3 S 1 atoms (He * ), which were generated in an RF discharge [15,16]. The spin polarization of He * was performed by optical pumping (OP) [17].…”
Section: Sp-issmentioning
confidence: 99%
“…The spin-polarized He + ions were generated from Penning ionization of spin-polarized He 2 3 S 1 atoms (He * ), which were generated in an RF discharge [15,16]. The spin polarization of He * was performed by optical pumping (OP) [17].…”
Section: Sp-issmentioning
confidence: 99%
“…SP-ISS, using electron-spin-polarized 4 He + ions, was developed as a novel analytical method for spin arrangement (magnetic structure) at surfaces and interfaces. It was observed that the polarization of OP radiation, which is used to generate spinpolarized He + ions, greatly affected PHe + especially in the high density range of OP radiation.…”
Section: Resultsmentioning
confidence: 99%
“…The central component for the generation of electron spinpolarized 4 He + ions is Penning ionization of spin-polarized metastable He 2 3 S1 and 2 1 S0 atoms (He*) 4 :…”
Section: Sp-issmentioning
confidence: 99%
See 1 more Smart Citation
“…The present apparatus is described in detail elsewhere [4][5][6]11,12]. Briefly, spin-polarized He + ions extracted from an optically-pumped rf-excited helium discharge are formed into a beam by a series of electrostatic lenses and directed onto the target surface at an angle of incidence of h $ 45°to the surface normal.…”
mentioning
confidence: 99%